The effect of various molarity sodium hydroxide (NaOH) on the hydrosodalite formation from synthesis of Johor Kaolin, Malaysia by hydrothermal method - Sazali, Norsuhailizah; Harun, Zawati; Azhar, Faiz Hafeez; Bahri, Syamsutajri Syamsol; Raja Ahmad, Raja Puteri Nurul Adibah; Hussin@Isa, Rosniza; Misdan, Nurasyikin (Elsevier, 2021)
In this present work, hydrosodalite was successfully synthesized by hydrothermal method from the raw Johor kaolin, Malaysia. In order to get the size that was less than 63 lm, the raw kaolin was ground and sieved. Since the raw kaolin did not undergo the beneficiation process, thus the raw kaolin then was calcinated for four hours at 650 C to produce more reactive clay (metakaolin). The synthesizing of hydrosodalite form of the metakaolin powder was conducted by mixing the powder with different molarities of sodium hydroxide, NaOH. This mixture was further treated by soaking it at a temperature of 40 C for 24 h. The reaction mixture was then moved for 12 h into the autoclave for the 100 C under hydrothermal conditions. The results through phase analysis via XRD, microstructure observation via SEM and bonding analysis via FTIR has revealed the existence of hydrosodalite phase in comparison with pure kaolin and metakaolin. The result also indicated the lower NaOH (4 M) molarity gave a higher percentage of hydrosodalite formation in comparison with higher molarity of NaOH at 5 M, 6 M and 7 M.